Experimental investigation of process parameters for the filtration property of nanofiber membrane fabricated by needleless electrospinning apparatus. (April 2021) - Wei, Liang; Yu, Haonan; Sun, Runjun; Liu, Chengkun; Chen, Meiyu; Liu, Huijing; Xiong, Jian; Qin, Xiaohong
In recent years, mass production of nanofiber has attracted attention of many researchers. Needleless electrospinning technology has been studied and developed to fabricate high-yield nanofibers, which could overcome the shortages of traditional single electrospinning apparatus, such as low efficiency, uneven nanofiber membrane, and difficulty in cleaning single needle. In this study, a novel needleless electrospinning apparatus was used to produce high-quality nanofiber membrane in terms of the features of small nanofiber diameter and narrow diameter distribution. Multiple jets were formed on the edge of the needleless electrospinning spinneret. The number of jets had a significant increase trend with the increase of the applied voltage. Wide-width nanofiber membrane could be fabricated by using this needleless electrospinning setup. This study also investigates the effects of process parameters on surface morphology, stress–strain, pore diameter, and filtration property of nanofiber membrane. This needleless electrospinning apparatus is suitable for industrialization production of nanofiber membrane.